DETECTION OF POTENTIALLY TOXIGENIC MICROCYSTIS STRAINS FROM DAU TIENG RESERVOIR - Luu, Pham Thanh; Quang, Ngo Xuan (Vietnam Journal of Biotechnology, 2018)
Microcystis is a bloom-forming, common cyanobacterium in Dau Tieng reservoir used for public water supply. To assess the presence of potentially microcystin-producing Microcystis, molecular techniques were conducted and acute toxicity bioassays were performed with the microcrustacean Daphnia magna exposed to cyanobacterial crude extracts. Potentially toxigenic of isolated strains was characterized by amplifying mcyD genes and identification of Microcystis was confirmed by 16S rRNA amplification. Microcystins (MCs) concentration in bloom samples and cultured strains were quantified by High Performance Liquid Chromatography (HPLC). Results showed that there were 9/15 strains showed positive with the mcyD marker indicating that they are toxic strains. Three MCs variants including MC-RR, -LR and -YR were found in all extracts of toxic strains with the highest concentration of 1,218 μg/g dry weight (DW). The acute toxicity bioassays revealed that both toxic and non-toxic crude extracts elicited significant lethal effects on the tested animal with LC50 values ranged from 189-411 mg DW/L. The toxic effects of isolated strains were independent from the MCs concentration in some strains suggesting the presence of other metabolites contributed to the biological effects. In conclusion, microcystin-producing Microcystis from the Dau Tieng reservoir warn about possible toxic effects for aquatic biota and human health.